Peran Vitamin C dalam Pengobatan COVID-19 - Dimas Enggar Bimantara (Majority, 2020)
The World Health Organization (WHO) was informed on December 2019 about a coronavirus pneumonia outbreak in Wuhan, Hubei province (China). Subsequently, on March 12, 2020, 125,048 cases and 4,614 deaths were reported. Coronavirus is an enveloped RNA virus, from the genus Betacoronavirus, that is distributed in birds, humans, and other mammals. WHO has named the novel coronavirus disease as COVID-19. Currently, there is no vaccine or specific antiviral drug for this deadly disease. More than 80 clinical trials have been launched to test coronavirus treatment, including some drug repurposing or repositioning for COVID-19. Viral infections caused by coronavirus could evoke cytokine expression leads to activation of pulmonary capillary endothelial cells, neutrophil infiltration and increased oxidative stress. Vitamin C, an important component of cellular antioxidant systems, is beneficial for critical care management. Vitamin C can also kill and prevent viral replication. Several studies have shown the administration of vitamin C orally and intravenously can reduce the increased risk of complications, reduce the severity, overcome symptoms and improve the prognosis of patients with COVID-19.